Legal System Resilience in Afghanistan: Dynamics of Pluralism and Political Transformation - Agusti, Nailatul Fadhilah; Zulfan, Zulfan; Eva, Yusnita; Muhammad, Zakkiyu; Ahmad, Md Yazid (Kawanua International Journal of Multicultural Studies, 2024)
Afghanistan is a multiethnic country with a complex legal system characterized by intricate interactions between Islamic law, customary law, and modern legal frameworks. This research critically examines the resilience mechanisms of Afghanistan's legal and judicial systems within the context of persistent political uncertainty and societal pluralism. Employing a descriptive qualitative methodology and comprehensive literature review, the study analyzes legal documents, international reports, and academic literature spanning the post-Taliban period from 2001 to the present. The research investigates the dynamic challenges confronting Afghanistan's legal infrastructure, particularly its capacity to integrate diverse normative systems while maintaining institutional legitimacy. Key findings reveal significant complexities in Afghanistan's legal landscape. The system encounters substantial obstacles in harmonizing Islamic legal principles, traditional customary practices, and contemporary legal standards. Family law reforms emerge as a critical focal point, demonstrating progressive attempts to enhance women's rights while simultaneously navigating conservative societal resistance. The research illuminates the intricate interplay between legal pluralism, political transformation, and institutional adaptation. It highlights how Afghanistan's judicial system continuously negotiates between preserving traditional legitimacy, accommodating societal diversity, and meeting international normative standards. The study recommends a comprehensive, nuanced approach to judicial reform that holistically considers cultural diversity, respects traditional values, and aligns with international human rights principles. By exploring the mechanisms of legal resilience in a conflict-affected context, this research contributes valuable insights into understanding adaptive strategies within complex, multi-layered legal systems. The findings provide a critical framework for comprehending how legal institutions can maintain functionality and relevance amid profound political and social transformations.